Cointegration Error Correction and the Dynamics of Canadian M2 and M2+ Demand - Aly F. Jiwan (Queen's University, Department of Economics, 1991)
Using the properties of integrated and cointegrated economic time series, this paper derives an error correction model (ECM) of money demand from a dynamic optimization problem. A general form of the ECM is estimated for Canadian M2 and M2+ over the period 1968:I to 1989:IV. The ECM appears to be a stable representation of broad money demand in Canada in terms of parameter constancy and forecasting ability. It is found that the demand for broad money in Canada is sensitive to the expected returns to holding foreign money. This result implies that the monetary authority should account for currency substitution in setting policy rules. The very low interest rate elasticities estimated indicate that a policy of interest rate targeting may be difficult to conduct since the spread between competing and own rates would have to be controlled.
Keywords: 330